Formation of Professional Competence of Teachers of “Upbringing” - Zulayxo Nazarova (Research Parks Publishers, 2021)
In recent years, the education system of our country has entered a new stage of development. Development of the education system has become a priority of the new state policy of Uzbekistan. The necessary base of opportunities has been created for the upbringing of a spiritually mature, mentally healthy and harmoniously developed generation